13 British artists children should know - Baverstock, Alison (Prestel, 2011)
"Colorful, chronologically arranged overview uses games, puzzles, and project ideas to encourage young people to appreciate the diverse ways in which British artists reflect their country's culture. Religious art, modern sculpture, exquisite landscapes and urban art are all presented in full-page spreads that engage children by inviting them into the works themselves, challenging them to answer questions about the artists' perceptions and exposing them to the fascinating historical forces that have shaped the artists' work"--Publishers website